Niacin supplementation attenuates the regression of three‐dimensional capillary architecture in unloaded female rat skeletal muscle - Hao Lin; Jihao Xing; Han Pan; Takumi Hirabayashi; Noriaki Maeshige; Ryosuke Nakanishi; Hiroyo Kondo; Hidemi Fujino (Physiological Reports, 2024)
Abstract Inactivity can lead to muscle atrophy and capillary regression in skeletal muscle. Niacin (NA), known for inducing hypermetabolism, may help prevent this capillary regression. In this study involving adult female Sprague–Dawley rats, the animals were randomly assigned to one of four groups: control (CON), hindlimb unloading (HU), NA, and HU with NA supplementation (HU + NA). For a period of 2 weeks, the rats in the HU and HU + NA groups underwent HU, while those in the NA and HU + NA groups received NA (750 mg/kg) twice daily through oral administration. The results demonstrated that HU lowered capillary number, luminal diameter, and capillary volume, as well as decreased succinate dehydrogenase activity, slow fiber composition, and PGC‐1α expression within the soleus muscle. However, NA supplementation prevented these alterations in capillary structure due to unloading by stimulating PGC‐1α factors and inhibiting mitochondrial dysfunction. Therefore, NA supplementation could serve as a potential therapeutic approach for preserving the capillary network and mitochondrial metabolism of muscle fibers during periods of inactivity.